Views on the Formation of the Main Tasks and Functions of the System of Command Bodies of the Operational Group of Troops in the Armed Forces of Ukraine - Kurtseitov, Tymur; Baranov, Serhiy; Remez, Volodymyr; Rybak, Dmytro; Samsonenko, Maksym; Yankovyi, Yaroslav (Social Development and Security, 2025)
Purpose. formation of views on determining a rational system of tasks and functions of the system of command bodies of the operational group of troops in the Armed Forces of Ukraine in operations (combat actions).Method. analysis; synthesis; abstraction and situational analysis (thinking).Findings. an analysis of the available scientific and analytical literature, as well as combat experience and doctrinal and normative basis on the issue of the distribution of tasks and functions of the system of command bodies of the operational group of troops in the Armed Forces of Ukraine was conducted; the main tasks and functions of the system of command bodies of the operational group of troops in the Armed Forces of Ukraine were determined in accordance with J-structures.Theoretical implications. The results of the study can be used to improve the functional structures of the military command bodies of the operational-strategic level of command in the Armed Forces of Ukraine.